Convenor - Manganaris, George A. (My University, 2026)
Organization body: European Cooperation in Science & Technology (COST) Capacity: Convenor Dates: 26-28 November 2019 Place: Lemesos, Cyprus Delegates: 100 The final meeting of COST Action CA15136 was a joint initiative of CUT and AUA (Prof. Serkos Haroutounian). The Scientific Program was comprised by 8 plenary talks and 56 oral/flash oral presentations, covering the whole spectrum of research on carotenoids. Conference website provides information about keynote speakers, scientiofic program. Exceptionally, the electronic book of abstracts is available on line.